Analysis of a Special, 3D Metal-Printed HPDC Tool Material - Kovács, Sándor Endre; Varga, László; Szentes, Zsolt (International Journal of Engineering and Management Sciences, 2020)
High Pressure Die Casting (HPDC) is still the most productive metal-casting method of our time, however the more demanding are the industrial expectations, the more challenging it becomes to ensure the creation of the difficult cavity geometries and the thermal balance of the die-cast tool. New perspective is required, thus we can utilize high heat-conductivity tool steels and additive manufacturing technology.